PENGARUH KAMPANYE NEGATIF DAN KEBERPIHAKAN CALON PETAHANA KEPADA PEMODAL TERHADAP PERILAKU MEMILIH KOTAK KOSONG (STUDI KASUS PILKADA KABUPATEN PATI 2017) - Sari, Melina Vasni Jovita; ., Fitriyah (Journal of Politic and Government Studies, 2019)
The reasearch is a set of interest by the selection region head of Pati regency 2017, which only followed by a couple of candidates, Haryanto (incumbent candidate) and Saiful Arifin, to fight an empty box. The empty box on the polling station gets 25,48% votes. This votes is significant other than 9 other areas that were also only followed by a single candidates by then. In addition, the volunteer of empty box is sufficiently active to select an empty box and do a negatif campaign about incumbent’s candidate. And the prospective incumbent’s candidate to investors has been identified as one of the unchosen selecting of empty box. The methods used in this research are quantitative methods of research with statistical tests as a tool to test hypotheses. The purpose of this research is to know whether there is a partial or shared influence of a negative campaign, the prospective incumbent’s candidate to the investors, and the behavior of choosing empty box on the selection of Pati regency 2017.The results of this research indicates that there is influence between the negative campaign to behavior of choosing empty box, there is influence between the prospective incumbent’s candidate to investors to choosing empty box, and together there is influence between the negative campaign and the incumbent’s candidate to the investors to choosing empty box on the selection region head of Pati regency 2017. In a hypotheses test the influence of both variables, there are negative campaign and the prospective incumbent’s candidate to the investors, to the behavior of choosing empty box are 42,3%, and 57,7% are described or influenced by other variables beyond the research.Keywords : The Selection of Pati Recency 2017, Negative Campaign, The Prospective Incumbent’s Candidate To Investors, Behavior of Choosing Empty Box